2013
DOI: 10.3892/ol.2013.1667
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-32 inhibits the proliferation and invasion of the SGC-7901 gastric cancer cell line in vitro

Abstract: microRNAs (miRNAs) are a class of endogenously expressed, small non-coding RNAs, which suppress their target mRNAs at the post-transcriptional level. miRNAs play key roles in tumor metastasis. The aim of the present study was to investigate the expression of miRNA-32 (miR-32) on the biological behavior of the human gastric cancer cell line, SGC-7901. SGC-7901 cells were transfected with miR-32-mimic, miR-32-inhibitor and empty plasmid vectors using Lipofectamine™ 2000. The expression of GFP was observed by flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Previous studies have demonstrated that certain miRNAs are correlated with the proliferation and survival of HCC, including miR-7, miR-124, miR-122, miR-26a, and miR-199 [10][11][12][13]. Notably, previous studies have demonstrated that overexpression of miR-32 greatly inhibits the proliferation and decreases the migration and invasion capabilities of SGC-7901 cells in vitro [14]. Additionally, it has been reported that miR-32 was significantly down-regulated in osteosarcoma tissues, compared with the adjacent normal tissues, and it could inhibit osteosarcoma cell proliferation and invasion by targeting Sox9 [15].…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have demonstrated that certain miRNAs are correlated with the proliferation and survival of HCC, including miR-7, miR-124, miR-122, miR-26a, and miR-199 [10][11][12][13]. Notably, previous studies have demonstrated that overexpression of miR-32 greatly inhibits the proliferation and decreases the migration and invasion capabilities of SGC-7901 cells in vitro [14]. Additionally, it has been reported that miR-32 was significantly down-regulated in osteosarcoma tissues, compared with the adjacent normal tissues, and it could inhibit osteosarcoma cell proliferation and invasion by targeting Sox9 [15].…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, miR-375 is associated with drug resistance in ovarian (71) and cervical cancer (72). Although no study has reported the role of miR-32 and -217 in drug resistance, it is associated with drug resistance-related processes such as cell proliferation, invasion and migration (73)(74)(75). Collectively, among the 7 microRNAs most strongly targeting HNF1B, the majority were involved in drug resistance in ovarian and other types of cancers, suggesting that the gene also mediates drug resistance.…”
Section: Microrna-mrna Interaction Analysis Indicating the Associatiomentioning
confidence: 99%
“…MiR-96 promoted cell proliferation of breast cancer by targeting RECK [14]. Herein, we focused on miR-32, which acted as either a tumor suppressor or a tumor promoter in different types of human cancers [15,16]. In this study, we found that miR-32 expression was markedly upregulated in breast cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 84%